Prawo nabycia w świetle nowej ustawy o kształtowaniu ustroju rolnego - Stańko, Marek (Wydawnictwo Naukowe UAM, 2015)
The subject of the paper is an analysis of the provision of Article 4 of the new Act of 5 August 2015 on the Shaping of the Agricultural Regime. The results of the study show that the mechanisms shaping the agricultural regime must be once again revised, including the ‘right to acquire’ land. The regulation of Article 10 of the 2015 Act has not removed or clarified the doubts arising from the provision of the 2013 Act on the Shaping of Agricul-tural Regime. Thus a question may be asked whether the right of acquisition is an effective tool for the shaping of the agricultural regime, especially since it has been very infre-quently resorted to by the Agency for Agricultural Land. Another question concerns the rationale for exempting close relatives from the right to acquire, or whether the right of acquisition should not be restricted in some other way. The paper ends with a recommen-dation that legislative work be commenced with a wider and more complex approach to the Act on the Shaping of the Agricultural Regime.

L’oggetto delle considerazioni è il diritto d’acquisto previsto anche nella nuova legge del 5 agosto 2015 sulla configurazione dell’ordinamento agrario. Ad analisi eseguita l’Autore afferma che è opportuno rivalutare i meccanismi di configurazione dell’ordina-mento agrario, tra i quali si colloca anche il “diritto di acquisto” del fondo. La regola-mentazione giuridica in esame, contenuta nell’art. 10 della legge del 2015, non chiarisce in alcun modo i dubbi apparsi nel contesto dell’art. 4 della legge del 2003 sulla configu-razione dell’ordinamento agrario. In particolare si pone la questione se il diritto di acquisto sia uno strumento efficace per la configurazione dell’ordinamento agrario dal momento che l’Agenzia per i Fondi Agricoli se ne serva di rado, ed anche se sia fondato escludere dalla cerchia di persone prossime i conviventi, se l’ambito di applicazione del diritto di acquisto non dovrebbe essere sottoposto a limitazioni apportate attraverso l’esclusione di alcuni contratti (p.es. un contratto a vita). A parere dell’autore è indicato intraprendere lavori legislativi di vasta portata per creare una legge completa sulla configurazione dell’ordinamento agrario.
The right of acquisition in light of the new Act on the Shaping of the Agricultural Regime
Il diritto di acquisto alla luce della nuova legge sulla configurazione dell’ordinamento agrario